2017
DOI: 10.1007/s11356-017-9948-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature stress: is phytohormones application a remedy?

Abstract: Among the various abiotic stresses, low temperature is one of the major environmental constraints that limit the plant development and crop productivity. Plants are able to adapt to low-temperature stress through the changes in membrane composition and activation of reactive oxygen scavenging systems. The genetic pathway induced due to temperature downshift is based on C-repeat-binding factors (CBF) which activate promoters through the C-repeat (CRT) cis-element. Calcium entry is a major signalling event occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 216 publications
0
34
0
Order By: Relevance
“… Kaya et al (2006) reported that drought tolerance can also be enhanced by the application of GA 3 in maize. Exogenous GA 3 application breaks the rosette by rapid enlargement of differentiated tissues under cold stress ( Khan et al, 2017 ). Similarly, JA has been reported to trigger the plant defense responses to abiotic stresses including drought and chilling ( Pauwels et al, 2009 ; Seo et al, 2011 ).…”
Section: Management Strategiesmentioning
confidence: 99%
“… Kaya et al (2006) reported that drought tolerance can also be enhanced by the application of GA 3 in maize. Exogenous GA 3 application breaks the rosette by rapid enlargement of differentiated tissues under cold stress ( Khan et al, 2017 ). Similarly, JA has been reported to trigger the plant defense responses to abiotic stresses including drought and chilling ( Pauwels et al, 2009 ; Seo et al, 2011 ).…”
Section: Management Strategiesmentioning
confidence: 99%
“…This is possibly due to the higher carbohydrate content used as an energy reserve and the role of plant hormones in regulating plant adaptation to low temperatures [70]. Under low-temperature stress, cytokinin content in Carpobrotus edulis increases [71] and an Arabidopsis mutant amp1 with higher cytokinin levels can display a better relative growth rate and higher plant yield than wild-type [72,73]. At the same time, overexpression of AtCOR15a:ipt in sugarcane improves tolerance to low temperatures by slowing leaf senescence and reducing membrane damage, avoiding severe productivity loss and freezing injury [74].…”
Section: Cold Stress Responsementioning
confidence: 99%
“…Cucumber is widely cultivated in greenhouses in northern China during the winter and spring seasons. Low temperature is a crucial environmental factor that limits the development and productivity of cucumber crops [ 3 ].…”
Section: Introductionmentioning
confidence: 99%